Serving with a Passion - Devendra, Kiran (THE PRIMARY TEACHER, 2011)
My younger brother’s wife Queenie was going to AktivOrtho for her spinal problems, where its Chairman and Managing Director, Dr Gerd Mueller, an orthopaedic surgeon of international repute, convinced her that she could get better with graded active and passive treatment. The moment Queenie learnt this, she thought of my spinal problem which was twelve years old, and was making me undergo a lot of pain which was showing in my eyes and face. When she told me that I needed to see Dr Mueller, I was uncomfortable and hesitant. I did not want to leave my coping mechanism, a comfort zone which I had developed for myself over the years. However, after an hour or two, she told me that it was up to me to decide, but I must try to meet the doctor who was mature and grounded.